Single Well Petrophysical Analysis: A Case Study of Belle Fourche Shaly-Sand, Hatton Gas Field, Southwest Saskatchewan - Derder, Omar M. (Scientific Journal of University of Benghazi, 2021)
This case study shows the petrophysical evaluation of the Belle Fourche Formation, Hatton Gas Field, Southwest Saskatchewan, using conventional well log interpretation techniques. The Belle Fourche reservoir analysed is indicated as shaly-sand formation, while petrophysical parameters calculated includes gross thickness, net thickness, volume of shale, porosity, and water saturation. Cross plots, in conjunction with previous core sedimentology study was used to identify lithology as shale dominated by mixed clay. The potassium content remains relatively constant as the clay content increases. In contrast, the thorium content increases with an increase in the clay content presenting thorium potassium ratio of 12, composed of montmorillonite and mixed-layer clay. Shale content increases as the thorium and uranium content increases. Results from the petrophysical evaluation revealed a gross reservoir thickness of 6.36 m, an average net shaly-sand thickness of 2.13 m, an average volume of clay of 13 %, the porosity of 15 %, and average water saturation of 43 %. Rock petrophysics cross plot of density versus P-wave (Vp) velocity was attempted to identify hydrocarbon saturation. The calculated velocities using the Greenberg and Castagna relation indicate slight increase in Vp and a decrease in density in shaly-sand data indicating hydrocarbon saturation in the reservoir interval. This paper has presented conceptually simple petrophysical method, structured in a manner that is easy to understand for a shaly-sand formation evaluation.